Mythologization of The Goddess Mazu: Readings through Spacial Setting and Activity in the Interior of Cu An Kiong Temple - Triatmodjo, Suastiwi; Tsai, Ted Tsung-te; Burhan, M. Agus; Prasetya, Hanggar Budi; Budiarti, Endah (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2022)
This study aims to understand the myth of the Goddess Mazu in Lasem City, Central Java. The research was conducted by observing the interior space at Cu An Kiong (CAK), the oldest temple in Lasem City. This study uses a verbal communication approach from Rapoport (1982) and a cultural approach from Koentjaraningrat (2015) to explore human relations with their environment and explain phenomena that exist in the research object. The research found that there is an exaltation space in this Mazu temple; this space is placed on the axis of space and time, it is to see the meaning of the space that has been built is practiced by the whole community, both the Chinese and the Javanese ethnicities, in a continuous flow of time from the first time the temple was built until now, as well as providing an interpretation of the phenomenon which are actually happened in Lasem. Based on the research, it can be concluded that the exaltation space shows the mythical practice of the Goddess Mazu by the local community, both Chinese and Javanese ethnicities. The mythology of Goddess Mazu, or Mak Co, is the protector of fishermen, sailorman, and common people in Lasem.